2023
DOI: 10.1164/rccm.202302-0289oc
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Diagnostic and Therapeutic Opportunities for Chronic Obstructive Pulmonary Disease in Low- and Middle-Income Countries

Abstract: Rationale Chronic obstructive pulmonary disease (COPD) is a prevalent and burdensome condition in low- and middle-income countries (LMICs). Challenges to better care include more effective diagnosis and access to affordable interventions. There are no previous reports describing therapeutic needs of populations with COPD in LMICs who were identified through screening. Objectives To describe unmet therapeutic need in screening-detected COPD in LMIC settings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Self-management interventions for COPD that include action plans have shown variable results for improving respiratory disease–related quality of life and respiratory-related hospital admissions. However, pooled analyses have shown that such interventions can lead to improvements in these outcomes ( 3 , 27 ). Aboumatar and colleagues examined the effect of a transitional care and long-term self-management support intervention after discharge for individuals hospitalized for COPD in Baltimore, Maryland ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-management interventions for COPD that include action plans have shown variable results for improving respiratory disease–related quality of life and respiratory-related hospital admissions. However, pooled analyses have shown that such interventions can lead to improvements in these outcomes ( 3 , 27 ). Aboumatar and colleagues examined the effect of a transitional care and long-term self-management support intervention after discharge for individuals hospitalized for COPD in Baltimore, Maryland ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…These and other factors, such as existing workload and specific role within the overall health system, would influence intervention fit or required adaptations in a particular setting. Furthermore, in the absence of COPD medication availability ( 3 , 17 ), CHWs would be unable to carry out their duties in the distribution of evidence-based treatments. As such, task-shifting strategies should complement larger-scale structural reforms to improve the quality and accessibility of chronic disease treatment and care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Florman and colleagues are to be commended for drawing attention to the overwhelming burden generated by chronic obstructive pulmonary disease (COPD) in low- and middle-income countries ( 1 ). Access to the resources for its diagnosis and treatment are extremely limited, reflecting the reality in Nepal, Peru, and Uganda.…”
mentioning
confidence: 99%
“…In high-income countries, tobacco smoking contributes to 70% of the COPD cases, but in LMICs nonsmoking risk factors, such as exposure to biomass smoke, ambient air pollution, occupational exposures, recurrent respiratory tract infections during childhood, past history of pulmonary tuberculosis, poverty, poor nutrition, and poorly treated asthma account for 60–70% of the COPD burden ( 3 ). More than 90% of the patients with COPD in LMICs remain undiagnosed, untreated, or wrongly treated ( 4 ). Limited resources, lack of availability of proper diagnostic tools, poor access to affordable drugs, and overstretched healthcare systems contribute to poor quality of care in the LMICs.…”
mentioning
confidence: 99%